2013
DOI: 10.3389/fpsyg.2013.00273
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Actions

Abstract: Actions that are chosen have properties that distinguish them from actions that are not. Of the nearly infinite possible actions that can achieve any given task, many of the unchosen actions are irrelevant, incorrect, or inappropriate. Others are relevant, correct, or appropriate but are disfavored for other reasons. Our research focuses on the question of what distinguishes actions that are chosen from actions that are possible but are not. We review studies that use simple preference methods to identify fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 55 publications
(85 reference statements)
1
17
0
Order By: Relevance
“…Motor actions, such as reaching for and grasping objects, are often guided by the actor's anticipation of forthcoming postural and task demands. Studies on human and nonhuman primates have demonstrated that the rudimentary motor planning abilities appear to be shared across species (Rosenbaum et al, 2013). Interestingly, capuchins showed more pronounced motor planning abilities in tasks in which the principal axis of the graspable object was aligned with the horizontal plane (Zander & Judge, 2015;Sabbatini et al, 2016) compared with the vertical plane (Zander et al, 2013;Truppa et al, 2016).…”
Section: Motor Planning For Grasping Objectsmentioning
confidence: 99%
“…Motor actions, such as reaching for and grasping objects, are often guided by the actor's anticipation of forthcoming postural and task demands. Studies on human and nonhuman primates have demonstrated that the rudimentary motor planning abilities appear to be shared across species (Rosenbaum et al, 2013). Interestingly, capuchins showed more pronounced motor planning abilities in tasks in which the principal axis of the graspable object was aligned with the horizontal plane (Zander & Judge, 2015;Sabbatini et al, 2016) compared with the vertical plane (Zander et al, 2013;Truppa et al, 2016).…”
Section: Motor Planning For Grasping Objectsmentioning
confidence: 99%
“…This relates to the idea that, while not always acknowledged in the cognitive and movement science research communities, producing movement sequences is a cognitive task that also relies on central and perceptual processes (Rosenbaum, 2005;Rosenbaum, Chapman, Coelho, Gong, & Studenka, 2013). The various strategies to produce movement sequences do not only differ across participants, but even individual participants appear to sometimes switch between execution strategies (e.g., following an error; Jentzsch & Dudschig, 2008;Notebaert et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into manual asymmetries are not limited to the level of motor execution but have also been extended to the motor planning level. One intriguing domain in which motor planning can be studied is object manipulation (see Rosenbaum et al, 2012 , 2013 , for reviews). As the very same object can be grasped differently depending on whether one intends to use that object or to pass it to another person to use, differences in the way an object is grasped depending on different future task demands or action goals can be ascribed to differences in the respective action plans.…”
Section: Introductionmentioning
confidence: 99%